Implementasi Kebijakan Perlindungan Anak di Kota Pekalongan - Mafturrahman Mafturrahman; Budi Nugraha; Aria Elshifa; Yayi' Safira; Muhammad Fadhil Rasyid (Universitas Mataram, 2023)
Policies about effort Protection of Children beside Constitution Number 23 of 2002 in conjunction with Law Number 35 of 2014 on Child Protection in detail regulated by government regulations Number 59 of 2019 concerning Implementation of Coordination on Child Protection Problems with child protection The problem with child protection is that there are still many children who cannot enjoy their rights. This is proven in Central Java from the Central Java Statistics Agency (BPS) report, since 2021 there have been reports of complaints of neglected children totaling 10620 children having problems with law 451 and children who have been subject to acts of violence totaling 282. Data from the Pekalongan Dinkominfo Public Communication Team reported on January 14, 2022, there were 8 cases of violence against children. This research was conducted with the aim of explaining and analyzing the implementation of child protection in Pekalongan City Child Welfare Institutions (LKSA). This research uses a qualitative approach to solve the problems in this study, the descriptive method is related to the problems of Child Welfare Institutions (LKSA). The results explain that there are still many children with social welfare problems (PMKS) who need to get care at the Child Social Welfare Institution (LKSA) in Pekalongan City.